Stress, Metabolism and Cancer. Issue 2 (March 2015) - Repasky, Elizabeth A.; Eng, Jason; Hylander, Bonnie L.
<x xml:space="preserve">Abstract</x> Abstract The potential for immune cells to control cancers has been recognized for many decades, but only recently has real excitement begun to spread through the oncology community following clear evidence that therapeutic blockade of specific immune-suppressive mechanisms is enough to make a real difference in survival for patients with several different advanced cancers. However, impressive and encouraging as these new clinical data are, it is clear that more effort should be devoted toward understanding the full spectrum of factors within cancer patients, which have the potential to block or weaken antitumor activity by immune cells. The goal of this brief review is to highlight recent literature revealing interactive stress and metabolic pathways, particularly those mediated by the sympathetic nervous system, which may conspire to block immune cells from unleashing their full killing potential. There is exciting new information regarding the role of neurogenesis by tumors and adrenergic signaling in cancer progression (including metabolic changes associated with cachexia and lipolysis) and in regulation of immune cell function and differentiation. However, much more work is needed to fully understand how the systemic metabolic effects mediated by the brain and nervous system can be targeted for therapeutic efficacy in the setting of immunotherapy and other cancer therapies.